Perdebatan Maslahah Mursalah dalam Kitab-Kitab Al-Imam Al-Ghazali - Mohammad Hadi Sucipto; Khotib (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2020)
Al-Imam al-Ghazali had an important role in contributing thoughts about the Maslahah. Among his books in the field of Usul fiqh is, al-Mankhul, Syifa’ Ghalil and al-Mustashfa, in his three books he writes about the Maslahah, although some are described globally in one of his scriptures while in another book is written in detail. This resulted in the scholars ' debate about the view of al-Imam al-Ghazali. In the book al-Mankhul maslahat mursalah used the term al-Istidlal al-Mursal is a maslahah that there is no recognition of a proposition as a maslahah and also no rejection as a maslahah, not including the type recognized by the Shara ' and not by the purpose desired by Shara'. In the Book of Syifa' Ghalil using the definition of maslahah that there is recognition of the Shara ' although there is no specific evidence that recognizes the Maslahah and in the book Al-Mustashfa is to keep the purpose of Shara ', the purpose of Shara The controversy of the concept of Maslahah in the three books, Imam al-Ghazali practised the Maslahah daruriyyat, Maslahah hajjiyyat in the emergency position, Maslahah hajjiyyat and maslahah tahsiniyyat that there is recognition of Shara '.